The stranger's passage in cyberspace. - Murphree, HyonJoo Yoo (Postcolonial Studies, 2005)
Discusses the formulation of camp thinking that describes as encampment the spatialization of the bio-political technology that localizes and organizes political collectives solidifying specific class, race and nation-based interests. Assessment of the dualistic conflict between friends and enemies; Classification of cyberspace as an encampment that localizes and organizes corporate sovereignty; Evaluation of the universal state of exception in cyberspace.